Proactive early threat detection and securing Oracle Database with IBM QRadar, IBM Security Guardium Database Protection, and IBM Copy Services Manager by using IBM FlashSystem Safeguarded Copy - Shingornikar, Shashank; Bhandari, Raninder Ravi (IBM Redbooks, 2023)
This IBM® blueprint publication focuses on early threat detection within a database environment by using IBM Security® Guardium® Data Protection and IBM QRadar® . It also highlights how to proactively start a cyber resilience workflow in response to a cyberattack or potential malicious user actions. The workflow that is presented here uses IBM Copy Services Manager as orchestration software to start IBM FlashSystem® Safeguarded Copy functions. The Safeguarded Copy creates an immutable copy of the data in an air-gapped form on the same IBM FlashSystem for isolation and eventual quick recovery. This document describes how to enable and forward Oracle database user activities (by using IBM Security Guardium Data Protection) and IBM FlashSystem audit logs by using IBM FlashSystem to IBM QRadar. This document also describes how to create various rules to determine a threat, and configure and launch a suitable response to the detected threat in IBM QRadar. The document also outlines the steps that are involved to create a Scheduled Task by using IBM Copy Services Manager with various actions.